10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Firefighting requires high levels of aerobic fitness, muscular strength and endurance to perform demanding tasks under extreme conditions. Although previous research has focused mainly on general physical fitness, fewer studies have examined the impact of physical training interventions on task-specific performance. This systematic review aims to evaluate the effectiveness of structured physical training programs in improving firefighters' occupational task performance. Following PRISMA guidelines, a systematic literature search was conducted in October 2024 across PubMed, Cochrane, Web of Science and Scopus with no language or year restrictions. Searches used title/abstract fields (and keywords where applicable) with the phrase: ("Fireman" OR "Firefighter") AND ("Training" OR "Physical preparation" OR "Exercise program" OR "Physical fitness" OR "Task performance"). Eligibility criteria followed the PICOS framework: firefighters of any sex or experience, structured physical training interventions, outcomes measuring job-specific task performance and experimental study designs. Methodologic quality was assessed using the TESTEX scale. Five studies met the inclusion criteria. Interventions included high-intensity functional training, circuit training, nonlinear periodization and complex training. Across studies, these programs were associated with improvements in task performance, including reduced completion times in simulated fireground tests and enhanced proficiency in victim rescue, hose advancement and ladder operations. Structured, occupation-specific physical training programs appear to be associated with improvements in firefighters' task performance. Future research should compare protocols, refine training duration and progression and consider contextual factors such as baseline fitness and concurrent job demands.